Management of projects and programs content on competitiveness increase of ukrainian gas turbine building - Ryzhkov, S. S.; Рыжков, С. С.; Koshkin, K. V.; Кошкин, К. В.; Chernova, L. S.; Чернова, Л. С. (My University, 2014)
In the article the main directions of content management of projects and programs on the competitive growth of gas and turbine building industry have been defined. The com-petitive strengths for “Zorya”–“Mashproekt” products in the energy area for gas pipeline systems and ship GTEs are analyzed. A mathematical model is developed and the method for the rational projects portfolio formation at the enterprise which produces the GTI is pro-posed. Taking into account the capacity range of engines, the dynamics of supply of GTSPC “Zorya”–“Mashproekt” products applied to the stable tapped markets is studied. The methods of the GTE competitive growth by means of modernization of the operated ones and deve-lopment of the new ones are considered. A concept of formation of competitive production program of Ukrainian gas turbine enterprise is proposed.
Управление содержанием проектов и программ повышения конкурентоспособности украинского газотурбостроения
Ryzhkov, S. S. Management of projects and programs content on competitiveness increase of ukrainian gas turbine building = Управление содержанием проектов и программ повышения конкурентоспособности украинского газотурбостроения / S. S. Ryzhkov, K. V. Koshkin, L. S. Chernova // Shipbuilding & Marine Infrastructure. – 2014. – № 2 (2). – P. 35–46.
Keywords: gas turbine building; competition; projects and programs; production program; газотурбостроение; конкуренция; проекты и программы; производственная программа